Cost management: bibliometrics in the annals of the national production engineering meeting - Leite de Oliveira , José Nilton; de Souza Júnior , Armando Araújo; Albuquerque de Oliveira, Marcelo; de Mattos Veroneze, Gabriela; Kennedy Vieira, Raimundo; Luiz Reis, Dércio (International Journal for Innovation Education and Research, 2020)
The National Meeting of Production Engineering (ENEGEP) is an event organized by the Brazilian Association of Production Engineering (ABEPRO) in which brings together the academic community of researchers working in the sector of Production Engineering and constitutes one of the leading promoters of technical and scientific production in the area. Among the various topics transiting the meeting, cost management is one of those who has relevant interaction. This article aims to analyze the academic contributions published in the Annals ENEGEP from 2008 to 2018 and trends in the area of ​​Economic Management, Cost Management subarea. Methodologically it made the use of bibliometric analysis techniques, analyzing, quantitatively and qualitatively, 219 articles, considering the following variables: quantitative evolution of publications; authoring features per article; authors; educational institutions; keywords; and themes. The main results identified an average of twenty papers per year with the cost management issue, the vast majority of publications were carried out with two or more authors, in relation to the authorship, 71% of authors had only one article, the southern region is the one most representative authors of publications, and as to the keywords which is evident most frequently are "Cost Management" and "costs".